2023
DOI: 10.1002/ski2.213
|View full text |Cite
|
Sign up to set email alerts
|

Where and how have written action plans for atopic eczema/dermatitis been developed and evaluated? Systematic review

Abstract: Background Atopic eczema/dermatitis is a common inflammatory condition which affects 15%–30% of children and 2%–10% of adults. It can have a significant impact and its management can be challenging. It is important for patients, parents, and caregivers to know how to look after their skin. Objectives To identify and review written eczema action plans (WAPs) that are available internationally for use by patients, parents, and caregivers. Methods We followed Preferred Reporting Items for Systematic reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A number of solutions have been offered to date to address barriers for poor medication adherence, such as patient education, medication simplification, and telemedicine. Research investigating action plans as educational tools for managing pediatric AD or teledermatology revealed that the effectiveness of these measures was either unexamined or considered insignificant [ 4 , 5 ], with a notable absence of reports on how treatment simplification impacts patients’ adherence. In a systematic review of 11 studies exploring the therapeutic adherence of mobile apps, 7 studies confirmed that use of the mobile app increased treatment adherence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of solutions have been offered to date to address barriers for poor medication adherence, such as patient education, medication simplification, and telemedicine. Research investigating action plans as educational tools for managing pediatric AD or teledermatology revealed that the effectiveness of these measures was either unexamined or considered insignificant [ 4 , 5 ], with a notable absence of reports on how treatment simplification impacts patients’ adherence. In a systematic review of 11 studies exploring the therapeutic adherence of mobile apps, 7 studies confirmed that use of the mobile app increased treatment adherence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%